Faktor Penentu Penyesuaian Diri pada Mahasiswa Baru Emerging Adulthood Tahun Pertama dan Tahun Kedua - Patricia Febriani Oetomo; Listyo Yuwanto; Soerjantini Rahaju (Jurnal Ilmiah Psikologi MIND SET, 2017)
Problems that faced by the new college students both in the first year and second year in adjusting to college are friendship issues, lack of confidence, communication with others, anxious during exams and presentations, and more. The existence of various problems faced makes the individual experiencing barriers to adjust to the new environment. Therefore, this research is conducted to find out the determinants of adjustment for new students, especially for new students in the first year and second year in the development stage of emerging adulthood. The sample of this study amounted to 197 students who are new students in the first year and second year at the University of Surabaya by using sampling technique proportional stratified incidentally. The data collection method was using questionnaire of self-adjustment determinants and a self-adjustment questionnaire from Baker and Siryk (1986). The results showed of the 36 factors that formulated based on elicitation theory and interview with respondents finally forms 5 new factors. The new factors that determine the adjustment of new students are academic anxiety, competence and motivation, physical and psychological barriers, friendship, and openness and confidence. Dominant factors that can predict the ability of individuals to adjust themselves are physical and psychological barriers. This factor can affect the individual in solving the problems they face and become a barrier of themselves to adjust to the new environment.